Modeling the groundwater level for an arid aquifer under different groundwater management scenarios - Karim Soliman (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Groundwater is considered the only source of water in arid climate regions. Additionally, population growth is stressing the groundwater resources in the study area, especially in these regions leading to excess groundwater exploitation to meet the demands (domestic, and agricultural). Thus, the groundwater level may decline in the future causing a water scarcity problem. In order to overcome this problem, it is worth necessary to perform mitigation measures prior to raising the groundwater level by augmenting the groundwater in the hydrogeological system. Mitigation measures might be reducing the abstraction rate and installing new artificial recharge sites. To assess the potential of these measures, numerical modeling can be applied. Gaza strip aquifer was chosen as a case study due to the following reasons: arid aquifer, significantly stressed due to over-exploitation of groundwater. Different researchers have already proposed different management scenarios considering these mitigation measures, but most of them considered unreliable management scenarios to predict future groundwater. Some of them reduced the abstraction rate which will lead to the loss of agricultural lands. Whereas, the others increased the artificial recharge rate which is unfeasible to implement in the study area for the next 20 years. Hence, we applied numerical modeling in this article to predict the future groundwater level based on these mitigation measures taking into account reliable management scenarios according to the study area's current situation . The results indicate that combining both reducing the abstraction rate and increasing the artificial recharge is so promising and they were compared with the latter obtained by the previous researchers.